Best approximations of the Cauchy – Szegö kernel in the mean on the unit circle - Savchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We compute the values of the best approximations of the Cauchy – Szeg¨o kernel in the mean on the unit circle byquasipolynomials with respect to the Takenaka – Malmquist system.